A case report of severe cardioinhibitory reflex syncope associated with coronavirus disease 2019. Issue 1 (3rd January 2022) - Beil, Johannes; Gatti, Alessia; Leonhard, Bruch; Schroer, Hinrich
Abstract: Background: Coronavirus disease 2019 (COVID-19) has been recognized as a disease with a broad spectrum of clinical manifestations. In this report, we illustrate an extraordinary case of severe cardioinhibitory reflex syncope with prolonged asystole associated with COVID-19. Case summary: A 35-year-old male patient presented to the emergency department with a 10-day history of postural syncope and fever. Electrocardiogram monitoring during positional change revealed reflex syncope with cardioinhibitory response, exhibiting sinus bradycardia, subsequent asystole, and syncope. The patient tested positive for severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) and was admitted to the intensive care unit where temporary transvenous pacing was necessary because of prolonged episodes of asystole. Work-up included extensive cardiac and neurological diagnostic testing, but did not yield any structural abnormalities. Although temporary pacing was able to abort syncope, a decision was made to hold off on permanent pacing as the most likely aetiology was felt to be temporary cardioinhibitory reflex syncope associated with COVID-19. The patient was discharged with mild symptoms of orthostatic intolerance and responded well to education and lifestyle modification. Outpatient follow-up with repeat tilt testing after 3 and 6 months initially showed residual inducible syncope but was eventually normal and the patient remained asymptomatic. Discussion: We believe that autonomic imbalance with a strong vagal activation due to acute SARS-CoV-2 infection played a pivotal role in the occurrence of transient syncope in this patient's condition. Although pacemaker implantation would have been a reasonable alternative, a watch-and-wait approach should be considered in similar instances.